ANALISIS FAKTOR-FAKTOR DAYA TARIK WISATA BALI DAN IMPLIKASINYA TERHADAP PERENCANAAN PARIWISATA DAERAH BALI - I MADE SURADNYA (Program Studi Agribisnis, Fakultas Pertanian, Universitas Udayana Jalan PB.Sudirman Denpasar, Bali, Indonesia. Telp: (0361) 223544 Email: soca@unud.ac.id, 2006)
This policy research focuses on exploring the factors that attract foreign tourists tovisit Bali and to discuss its implications on planning of Bali as a tourism destination. At themoment the tourism development planning is mainly based on the supply side, that is theresources available in the region. However, due to the increase of competition and thedemanding tourists more comprehensive planning base involving the demand side, i.e.expectations of the visitors are becoming of equally important for the success of the tourismplanning itself.A survey was conducted and 505 visitors from the main tourist generating countrieswho visited Bali during peak and low season visit in 2005 participated the survey. Therespondent were randomly selected when they were at the waiting room at the Ngurah RaiAirport before leaving the country. The factor analysis successfully explored 8 factors thatattract foreign visitors to visit Bali, e.i. (1) Reasonable price of tourism products, (2)Cultural attractions, (3) Beach attractions, (4) Convenience traveling, (5) Relaxingenvironment, (6) Image of Bali as a tourist destination, (7) Natural beauty, and (8)Hospitality of local people.Based on the research findings, it is strongly recommended that in developing Balias a world class tourist destination, the tourism planner should consider those factors in theplanning process in order to better serve the more demanding tourists and the increase ofcompetition among tourist destinations.